THROMBO- EMBOLIC RISK IN HIGH ESTROGENIC PHASE OF NORMAL MENSTRUAL CYCLE IN HEALTHY WOMEN - Aftab, Muhammad Tariq; Shakeel, Saba; Tariq, Hira (Journal of Postgraduate Medical Institute, 2015)
Objective: This study is conducted to compare the risk of thrombo-embolism during different phases of menstrual cycles. Methodology:105 healthy premenopausal unmarried females of 18 -21 years with a history of previous three normal menstrual cycles and 32 age matched male volunteers were recruited in the study. The phase of menstrual cycle of female volunteers was established by taking menstrual history. Bleeding time was determined by Duke's method. Results: Bleeding time in 105 females was 73.03±1.89 Seconds and in 32 males was 69.33±4.94 Seconds which were not significantly different statis-tically (p=0.063). Among females, 69 volunteers were in follicular phase of their hormonal cycle. Bleeding time in 29 females in early follicular phase was 70.86±3.38 Seconds and 40 females in late follicular phase was 68.25±4.03 Seconds. Statistically significant difference was not seen (p=0.095) when the two phases were compared. Bleeding time is not found to be reduced in late follicular phase as compared to early follicular phase, even high concentra -tion of estrogen is present in the body in this phase as per normal menstrual physiology. Conclusion: High Estrogen in normal menstrual cycle does not increase thrombo-embolic risk in healthy women.